Analisis Pelaksanaan Pendelegasian Kewenangan Klinis Perawat di Rumah Sakit - Sitti Rahmatiah; Takdir Tahir; Kadek Ayu Erika (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This literature review aims to summarize the results of research regarding the implementation of delegation of clinical authority to nurses in hospitals. Literature search using five databases PubMed, ProQuest, ScienceDirect, Google Scholar and Wiley in the period 2013-2023. Nine studies were included in the review, where the effectiveness of the implementation of delegation of nursing authority could be hampered by three factors: 1) practice standards and policies (clarity of delegation standards, clarity of nurses' duties, transparent supervision); 2) delegation (delegator's fear of responsibility, burdensome delegation tasks, accountability, recognition of the delegate's efforts, education and learning opportunities, expertise, lack of positive incentives, communication and openness of information, trust); 3) situational obstacles (lack of resources, workload and fatigue, important tasks that are difficult to delegate). In conclusion, there are three factors inhibiting the effectiveness of delegation, namely: practice standards and policies, delegation, and situational obstacles. Keywords: Delegation, Clinical Authority, Implementation, Nurse, Hospital